Pengaruh Motivasi Divisi karyawan Marketing Terhadap Tingkat Penjualan - ., Syahyono (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2016)
The pursposes of the study is to determine the effect of Motivation On The Sales Division Level employees at PT.Sinar Griya Utama . The foregoing can not be achieved if there is no good cooperation among employees and the company so that a good motivation between superiors and subordinates to achieve the objectives of the company . Motivation as a human impulse to an action is very important advance in line with the duties and functions of employees. Impulses that exist on employees, whether they arise from himself and outside himself affect greatly on motivation. Good sales level is achieved caused by the training so that employee motivation has a spirit to achive of sales level. This study aims to identify and obtain a description as well as stating the role of employee motivation on the level of sales PT . Sinar Griya Utama